2018
DOI: 10.1186/s12917-018-1601-2
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus does not express viral microRNAs in experimentally infected pigs

Abstract: BackgroundAfrican swine fever virus (ASFV) is the etiological agent of African swine fever (ASF), a re-expanding devastating and highly lethal hemorrhagic viral disease. microRNAs (miRNAs) are a new class of small non-coding RNAs that regulate gene expression post-transcriptionally. The discovery of virus specific miRNAs has increased both in number and importance in the past few years. We have recently described the differential expression of several porcine miRNAs during in vivo infection with attenuated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…7a to c ). A previous in vivo study concluded that ASFV does not express viral miRNAs in experimentally infected pigs ( 31 ). However, the previous study restricted its analysis to miRNA only based on predictions of precursor miRNA structures and did not consider other classes of sncRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7a to c ). A previous in vivo study concluded that ASFV does not express viral miRNAs in experimentally infected pigs ( 31 ). However, the previous study restricted its analysis to miRNA only based on predictions of precursor miRNA structures and did not consider other classes of sncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…These authors identified 12 miRNAs that were differentially expressed. In addition, a further study looked in vivo at the potential for ASFV to encode its own miRNAs and concluded that ASFV does not express miRNAs in vivo ( 31 ). In our study, we investigated the effect of ASFV infection on sncRNA in primary porcine alveolar macrophages in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…The obtained cDNAs or extracted DNA were used as templates for RT-qPCR and qPCR, respectively, on a CFX96 real-time polymerase chain reaction system (Bio-Rad, Hercules, CA, United States) using 2 × RealStar Green Power Mixture (containing SYBR Green I Dye; Genstar, Beijing, China). The primers used for determining the DNA level of ASFV replication by using p72 gene ( Nunez-Hernandez et al, 2018 ) were listed in Table 1 . The primers ( Arabyan et al, 2018 ) used for determining the mRNA level of ASFV replication by using the p72 and p30 genes were listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The putative target genes were related to immune responses, such as B and T cell receptor signaling pathways, natural killer cell-mediated cytotoxicity, or Fc gamma R-mediated phagocytosis, as well as with processes related to infection-related pathogenesis and virus-host interaction (131). In another in vivo study, the same authors assessed the potential for ASFV to encode its own miRNAs, with negative results (132).…”
Section: Immunitymentioning
confidence: 99%